2006
DOI: 10.1158/0008-5472.can-05-3143
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Arctigenin as an Antitumor Agent Having the Ability to Eliminate the Tolerance of Cancer Cells to Nutrient Starvation

Abstract: Tumor cells generally proliferate rapidly and the demand for essential nutrients as well as oxygen always exceeds the supply due to the unregulated growth and the insufficient and inappropriate vascular supply. However, cancer cells show an inherent ability to tolerate extreme conditions, such as that characterized by low nutrient and oxygen supply, by modulating their energy metabolism. Thus, targeting nutrientdeprived cancer cells may be a novel strategy in anticancer drug development. Based on that, we esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
344
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 309 publications
(350 citation statements)
references
References 28 publications
5
344
0
1
Order By: Relevance
“…Arctigenin, an active compound found in the seeds of burdock, has the ability to eradicate nutrient-deprived cancer cells (Awale et al, 2006). In addition to its board spectrum of activities on different cancer cell lines, e.g.…”
Section: Anti-cancer Activitiesmentioning
confidence: 99%
“…Arctigenin, an active compound found in the seeds of burdock, has the ability to eradicate nutrient-deprived cancer cells (Awale et al, 2006). In addition to its board spectrum of activities on different cancer cell lines, e.g.…”
Section: Anti-cancer Activitiesmentioning
confidence: 99%
“…In contrast, roots of Arctium lappa L. (Asteraceae) (burdock) have hepatoprotective activities (Chan et al, 2011;Predes et al, 2011) and extract of this herb has shown antiproliferative effects on various cancer cells (Predes et al, 2011;Wegiera et al, 2012). Purification of active compound from the seed extract of Arctium lappa has led to the identification of lignan arctigenin as tumor-specific agent showing cytotoxicity to gastric, liver, colon, starved pancreas, and lung cancer as well as leukemia cells (Awale et al, 2006;Chan et al, 2011;Matsumoto et al, 2006;Predes et al, 2011;Susanti et al, 2012). A remarkable antineoplastic activity has demonstrated also for the extract prepared from Inula helenium L. (Asteraceae) roots revealing toxicity toward different tumor cell lines, including gastric, colon, liver, pancreas, mammary, and cervical cancer as well as astrocytoma, leukemia and melanoma cells (Dorn et al, 2006).…”
Section: Herbsmentioning
confidence: 99%
“…The root of Arctium lappa L, a popular edible vegetable in China and Japan, is used to make a general health tonic. Previous studies have shown that ATG exerted protective effects against oxidation [12] , viral infection [13] , and cancer [14] . Most recently, two research groups have reported that ATG could block the UPR and preferentially inhibit tumor cell viability under glucose-deprived conditions [15,16] .…”
Section: Introductionmentioning
confidence: 98%